Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1186/1745-9974-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical and mental health problems with chronic cough in a representative population cohort

Abstract: BackgroundAlthough chronic cough is a common problem in clinical practice, data on the prevalence and characteristics of cough in the general population are scarce. Our aim was to determine the prevalence of chronic cough that is not associated with diagnosed respiratory conditions and examine the impact on health status and psychological health, in a representative adult population cohortMethodsNorth West Adelaide Health Study (n stage 1 = 4060, stage 2 = 3160) is a representative population adult cohort. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
(90 reference statements)
0
14
0
5
Order By: Relevance
“…The improvement in depression scores following successful treatment of chronic cough suggests that depression, if present, may often be a side effect rather than a cause of cough. While psychological symptoms may be the result of chronic cough, cough and respiratory symptoms are more common in individuals with psychological morbidity (34,35). In a population cohort study (34) chronic cough was more common in those with psychomorbidity identified using the General Health Questionnaire-28.…”
Section: Psychomorbidity In Chronic Coughmentioning
confidence: 99%
“…The improvement in depression scores following successful treatment of chronic cough suggests that depression, if present, may often be a side effect rather than a cause of cough. While psychological symptoms may be the result of chronic cough, cough and respiratory symptoms are more common in individuals with psychological morbidity (34,35). In a population cohort study (34) chronic cough was more common in those with psychomorbidity identified using the General Health Questionnaire-28.…”
Section: Psychomorbidity In Chronic Coughmentioning
confidence: 99%
“…Indo ao encontro de uma pesquisa O Perfil Clínico e a Qualidade de Vida de Homens e Mulheres com Tosse Crônica com tosse atual, indicando uma relação significativa entre o tabagismo e a tosse atual 3 . Adams et al 16 citam ainda que a tosse crônica, do tipo seca, tem 1,7 razões de chances de acontecer em homens idosos (60 anos ou mais) do que em jovens (18 a 39 anos).…”
Section: Quadro 4 -unclassified
“…A maioria dos indivíduos relatou tosse, tipo produtiva, sendo que 14 (66.7%) eram mulheres e 07 (33,3%) homens. No estudo de Adams et al 16 , os indivíduos sem doença respiratória (n=2408), a tosse seca esteve presente em 249 (10,3%) nos homens e 176 (7,3%) em mulheres. Sendo que a tosse, tipo produtiva, ocorreu em aproximadamente 4,0% sem doença pulmonar diagnosticada 16 .…”
Section: Quadro 4 -unclassified
See 2 more Smart Citations